Transformação de Möbius : projeções na esfera de Riemann - Souza, André Luiz Braga de (2020)
In this work, the Möbius transformations will be studied in the set of complex numbers and using the Riemann sphere to assist in the visualization of the transformations and in the development and to present an activity proposal aimed at high school students about the geometric transformations that are the basis for the transformations of Möbius.